Analysis of the Attractiveness and Satisfaction of Visitors to Kasang Kulim Zoo After the Covid-19 Pandemic - Merny, Yanur; Genius Umar; Hendri; Rosdianto; Osronita; Linda Handayuni (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
Tourism is a strategic sector that contributes significantly to economic growth and regional development, but the COVID-19 pandemic has had a significant impact on tourism activities, including educational and conservation-based tourist destinations. This study aims to analyze the tourist attraction and visitor satisfaction at Kasang Kulim Zoo (KKZ), Kampar Regency, Riau Province, in the post-COVID-19 pandemic period. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results show that the appeal of KKZ is shaped by the diversity of its animal collection, educational and conservation values, natural environment, and family tourism experiences. Post-pandemic visitor satisfaction is influenced by the quality of facilities, cleanliness, comfort, safety, and the alignment between expectations and tourism experiences. Although visitor numbers show a recovery trend, challenges remain in terms of accessibility and facility management. Additionally, the presence of KKZ has a positive impact on the economic recovery of local MSMEs, making sustainable tourism management key to post-pandemic destination development.